Cinta Satu Marga di Tanah Karo Sebagai Inspirasi Penciptaan Naskah Drama Turang - Firety Yame L Br Sitepu; Philipus Nugroho Hari Wibowo; Rano Sumarno (Creativity And Research Theatre Journal, 2025)
The phenomenon of one clan's love in Tanah Karo is still alive and continues to develop in the current era. This is interesting to present from the perspective of a drama script, considering that drama performances are reflective and contentive in nature. Lajos Egri's writing theory is used as a theoretical framework for creating drama scripts, while the creation method used refers to Graham Wallas' creative method which consists of preparation, incubation, illumination and verification.Â  The Wallas method was chosen because there is a work testing point at the verification section, so that the drama script created can be refined based on constructive input.Â  The result of the creation is a manuscript entitled Turang which tells the story of a pair of lovers whose love is hindered by customs. They are unable to reject the understanding of their ancestors which states that love of one's clan will lead to a bad life.